2004
DOI: 10.1016/j.physa.2004.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Fractal geometry, information growth and nonextensive thermodynamics

Abstract: This is a study of the information evolution of complex systems by a geometrical consideration. We look at chaotic systems evolving in fractal phase space. The entropy change in time due to the fractal geometry is assimilated to the information growth through the scale refinement. Due to the incompleteness of the state number counting at any scale on fractal support, the incomplete normalization i p q i = 1 is applied throughout the paper, where q is the fractal dimension divided by the dimension of the smooth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Another method used to analyze the images was the structural similarity index (SSIM) [19]. This index is widely used in image processing to estimate the visual quality of digital images.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Another method used to analyze the images was the structural similarity index (SSIM) [19]. This index is widely used in image processing to estimate the visual quality of digital images.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The main aim is to find the relationship between the dimensions of the component fractals and the dimension of the composite fractal, and to see whether or not this relationship is dependent on the mixing manner. This question has been raised several years ago within a statistical theory called incomplete statistics (IS) which has been proposed by physical consideration in order to make statistics in, amount others, fractal phase spaces of dynamic systems [8,9,10,11,12,13]. A problem in this framework was to find the characteristic parameter (associated to the fractal dimension, see section 5.2 below) of a composite system from the same parameters of the component systems with the condition of the thermodynamic equilibrium [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction. Incomplete statistics (IS) proposed by Wang [1] and Tsallis' statistics [2,3] have been two important branches of nonextensive statistical mechanics [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recently, IS has been used to research the thermostatistic properties of a variety of physical systems with long-range interacting and/or long-duration memory and many significant results have been obtained [6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…Incomplete statistics (IS) proposed by Wang [1] and Tsallis' statistics [2,3] have been two important branches of nonextensive statistical mechanics [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recently, IS has been used to research the thermostatistic properties of a variety of physical systems with long-range interacting and/or long-duration memory and many significant results have been obtained [6][7][8][9][10][11][12][13][14][15][16]. For example, it has been found that for some chaotic systems evolving in fractal phase space [7,8], the entropy change in time due to the fractal geometry is assimilated to the information growth through the scale refinement; and that the generalized fermion distributions based on incomplete information hypothesis can be useful for describing correlated electron systems [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation